2020
DOI: 10.1016/j.jcf.2019.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient intake in children with cystic fibrosis in Sydney, Australia

Abstract: Background: Children with CF have been reported to consume significantly more energy-dense, nutrientpoor foods than controls where there are now concerns of inadequate micronutrient intake. There are no current or comprehensive dietary studies assessing micronutrient intake in CF children. Objectives: To evaluate micronutrient intake in children with CF compared to recommended dietary intakes (RDIs). Methods: Dietary intake of 13 micronutrients was measured in CF children aged 2-18 years and age-and sex-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…With reference to micronutrients, mineral intakes have not received adequate attention in CF, in contrast with the fat-soluble vitamins, which are routinely assessed in serum and supplemented orally [ 52 , 53 ]. Our patients exhibited comparable micronutrient intake with an Australian pediatric cohort of CF [ 54 ]. While for most micronutrients, the Australian study reported somewhat higher intakes than those we recorded, the largest differences were observed for vitamin A and magnesium intakes.…”
Section: Discussionmentioning
confidence: 76%
“…With reference to micronutrients, mineral intakes have not received adequate attention in CF, in contrast with the fat-soluble vitamins, which are routinely assessed in serum and supplemented orally [ 52 , 53 ]. Our patients exhibited comparable micronutrient intake with an Australian pediatric cohort of CF [ 54 ]. While for most micronutrients, the Australian study reported somewhat higher intakes than those we recorded, the largest differences were observed for vitamin A and magnesium intakes.…”
Section: Discussionmentioning
confidence: 76%
“…However, after the micronutrient consumption was energy-adjusted, only the riboflavin decreased compared to the mNICE diet. Micronutrient intakes may be quantified as absolute intake and energy-adjusted intake, which is the amount of the micronutrient per 1000 kcals [84]. The number of patients who met their dietary reference intakes did not change, with the exception of thiamin and iron in the LFD arm.…”
Section: Nutritional Adequacymentioning
confidence: 99%
“…Although the nutrition focus for CF is often on malnutrition due to malabsorption, other concerns are also being studied, such as micronutrient deficiency and the emerging concern of obesity. A cross sectional study (the Dietary Intake Study in cHildren (DISH), evaluated the dietary intake of 82 Australian children with CF compared to 82 healthy age and sex matched controls 6 . Children with CF consume more calories/energy, with increased absolute consumption of all micronutrients, except Vitamin C and folate.…”
Section: Nutritionmentioning
confidence: 99%